Research on Phthalic Acid Esters Removal and Its Health Risk Evaluation by Combined Process for Secondary Effluent of Wastewater Treatment Plant - Simin Li; Yongkang Lv; Na Zhao (The Scientific World Journal)
This paper analyses the treatment effect of the “coagulation-sedimentation-O3-biological sand filtration-GAC” combined process on phthalic acid esters in secondary effluent of municipal wastewater treatment plant and meanwhile evaluate its health risk. The results indicated that when the concentrations of DBP and DiOP in secondary effluent were at range of 0.41 mg/L–0.814 mg/L and 0.23 mg/L–0.36 mg/L, the average total removal rates of DBP and DiOP were 85.10% and 68.11%, and the average concentration of DBP and DiOP in effluent were 0.089 mg/L and 0.091 mg/L, respectively. The quality of the effluent met the requirement of the ornamental scenic environment water in The Quality of Urban Wastewater Recycling and Scenic Environment Water (GB/T 18921-2002), and the health risks of DBP and DiOP in effluent were at range of 1.99 × 10−12 –2.15 × 10−12/a and 1.48 × 10−11 –1.85 × 10−11/a, respectively, which is lower than the acceptable maximum risk level: 1.0 × 10−6.